Dispositivo de inovação no Ensino Superior: a produção do docentis innovatus e discipulus iacto - Rafaela Esteves Godinho (2017)
Innovation has become an imperative on contemporary society. Subjects are demanded to become innovators. For this, they carry their actions toward the meaning of changing, developing values, creating and, thus, innovating. It is possible to observe, then, an urgency on the production of innovator subjects, who must be active, participative, competitive and autonomous, for answering the demands inscripted on neoliberal rationality. With the goal of achieving this demand, university teaching is triggered on the production of these subjects. By this meaning, the current investigation had the objective of comprehending how is innovator docent produced on higher education. The researchs corpus is constituted by legislations (Constitutional Amendment 85/2015, Law nº 10.973, Law 13.243), public policies, edicts and, more specifically, Courses Pedagogical Projects of Medicine, Nursing and Physics graduations, from Minas Gerais Federal University and also the National Curriculum Guidelines of these courses. In addition, the analysis corpus was also composed by the professors formation course, named Formative Routes on Higher Education Teaching, offered by Innovation and Teaching Methodologies Directory, linked to UFMGs Pro-Rectory, ando also interviews developed with the participants/docents from the Routes. It was used, as theoretical reference, the post-structuralist perspective, specifically theoretical and analytical tools from philosopher Michel Foucault, such as: apparatus, discourse, power-knowledge and subject position. Through the methodological net, which has articulated elements from educational post-structuralist netnography, narrative interviews and the discourse analysis with Foucaults inspiration, I developed the general argument. According to that, innovation society, inscripted on neoliberal rationality, demands competitive, proactive and autonomous subjects. For corresponding to this demand, the innovation apparatus is triggered, with the university as its master gear and as its effect on the production of docentis innovatus and discipulus iacto subjects positions. It was verified that innovator teaching is regulated by constitutive marks, such as: using the formation by competences, acting as mediator of teaching-learning processes, incorporating digital technologies, focusing on learning and using active methodologies. These marks can act on the innovator teaching governance. Moreover, innovator docent is able to govern him/herself through operations which he/she can put on his/herself. Therefore, all these kind of others government product the docentis innovatus production. This dissertation show up that innovator teaching, through its constitutives marks, is on continuity with the production of active, competitive and proactive students - making available the discipulus iacto subject position - and it is on discontinuity with the fabrication of receptive, knowledge reproductor students - discipulus rustics when innovator teaching is answering neoliberal demands.